The performance of patients with cerebral microbleeds in different cognitive tests: A cross-sectional study - Li, Xuanting; Yang, Shuna; Li, Yue; Qin, Wei; Yang, Lei; Yuan, Junliang; Hu, Wenli (Frontiers in Aging Neuroscience, 2023)
Background The clinical features and pathological process of cerebral microbleed (CMB)-related cognitive impairment are hot topics of cerebral small vessel disease (CSVD). However, how to choose a more suitable cognitive assessment battery for CMB patients is still an urgent issue to be solved. This study aimed to analyze the performance of CMB patients on different cognitive tests. Methods This study was designed as a cross-sectional study. The five main markers of CSVD (including the CMB, white matter hyperintensities, perivascular spaces, lacunes and brain atrophy) were assessed according to magnetic resonance imaging. The burden of CMB was categorized into four grades based on the total number of lesions. Cognitive function was assessed by Mini-Mental State Examination (MMSE), Trail-Making Test (TMT, Part A and Part B), Stroop color-word test (Stroop test, Part A, B and C), Verbal Fluency Test (VF, animal), Digit-Symbol Substitution Test (DSST), Digit Cancellation Test (DCT) and Maze. Multiple linear regression analysis was conducted to analyze the association between CMB and cognitive findings. Results A total of 563 participants (median age of 69 years) were enrolled in this study, including 218 (38.7%) CMB patients. CMB patients showed worse performance than non-CMB subjects in each cognitive test. Correlation analysis indicated the total number of CMB lesions had positive correlations with the time of TMT, Maze and Stroop test, and negative correlations with the performance of MMSE, VF, DSST, and DCT. After the adjustment for all the potential confounders by linear regression, the CMB burden grade was correlated with the performance of VF, Stroop test C, Maze and DCT. Conclusion The presence of CMB lesions was associated with much worse cognitive performances. In VF, Stroop test C, Maze and DCT, the correlations between CMB severity and assessment results were more significant. Our study further confirmed that the attention/executive function domain was the most commonly evaluated in CMB, which provided a picture of the most utilized tools to analyze the prognostic and diagnostic value in CMB.